Etiology and treatment of periapical lesions around dental implants. (October 2014) - Temmerman, Andy; Lefever, David; Teughels, Wim; Balshi, Thomas J.; Balshi, Stephen F.; Quirynen, Marc
Abstract: The widespread use of oral implants in recent years has resulted in various types of complications. One of those complications is the periapical implant lesion. Different factors have been proposed to play a role in the development and emergence of a periapical implant lesion. To date, there is no consensus on the etiology and therefore periapical lesions around dental implants are considered to have a multifactorial etiology. The diagnosis of an implant periapical lesion should be based on both clinical and radiological findings. Additionally, in order to apply the best treatment strategy the evolution of the lesion should be taken into account. The treatment of this kind of lesion, however, is still empiric. Data, primarily from case reports, seem to indicate that the removal of all granulation tissue is a first step to arrest the progression of the bone destruction. The removal of the apical part of the implant seems a valuable treatment strategy.